Is performance appraisal to employee performance imperative? A bibliometric and systematic literature review - Binmlafikh, Mohammed Abdulmohsen; Wahab, Shah Rollah Bin Abdul; Al-Osaimi, Tariq Mohammed (Edelweiss Applied Science and Technology, 2025)
Performance appraisal assists employees in enhancing personal capabilities aligned with personal objectives and organisational goals. The paper seeks to provide comprehensive guidelines to academicians, policymakers, and organisations for effectively utilising performance appraisal to align employee performance with organisational goals. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework was followed when synthesising existing studies investigating the linkage between performance appraisal and employee performance. The Scopus database was the primary source of journal articles. A holistic keyword search identified 6,675 articles, which were filtered through inclusion and exclusion criteria. Consequently, 297 relevant articles were gathered. Equity theory, expectancy theory, and social exchange theory were primarily employed in the reviewed articles. Quantitative methodologies were the most popular approach, followed by mixed methods. Statistical analysis techniques, such as structural equation modelling and regression, also gained popularity. Furthermore, the reviewed articles encompassed various populations, sectors, and sample sizes when assessing the general applicability of performance appraisal while elucidating sector-specific challenges. This review contributed to the existing literature and suggested future directions for understanding performance appraisal and employee performance. The study recommended employing customised approaches, incorporating green HRM practices, and utilising innovative technologies to develop a more effective employee performance appraisal framework.